Artikel Review: Analisis Kadar Klorin pada Pembalut dengan Metode Volumetri - Sahara, Khalipatun; Nurohmah, Alivia; Maelaningsih, Firdha Senja; Cahyani, Lufitha Evelyne (Jurnal Medika Farmaka, 2023)
Introduction: Sanitary napkins are a hygiene product that women very commonly use during menstruation. The safety and quality of sanitary napkins are essential to prevent adverse impacts on health. One crucial aspect that needs to be considered is the level of chemical pollution, such as chlorine, which has the potential to endanger health. The volumetric method is one of the most commonly used methods to measure the chlorine content in various products. In this article, the volumetric method for analyzing chlorine content in sanitary napkins consists of three methods: iodometric titration, iodometric titration, and argentometric titration. This article aims to summarize a literature review that discusses various studies regarding the analysis of chlorine levels in sanitary napkins using the volumetric method. Method: The method used in the article review is a literature review by taking journal articles containing analysis of chlorine levels in sanitary napkins using the volumetric method. Results: A review of various studies showed variations in chlorine levels in the sanitary napkin samples tested. Conclusion: Chlorine levels in sanitary napkins can be analyzed using the volumetric method, with the chlorine results that can be analyzed being in the range of 0.0022% w/v-0.0022% w/v.